Peranan Audit Internal Dalam Meningkatkan Efektivitas Pengendalian Internal Persediaan - Efrianti, Desi; Nurjanah, Yayuk; Fajar, Zona (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
The Purpose of this research is to find out how the internal audit of inventory can increase teh efficiency and effectiveness on PT Fastfood Indonesia Tbk, in one of its branch outlet; KFC Ekalokasari as the object. PT Fastfood Indonesia Tbk is the only company that has the rights of trademark Kentucky Fried Chicken (KFC) in Indonesia. The KFC Ekalokasari stock of goods are raw materials (chicken, vegetables, flour, etc), walk in process (marinated chicken, verkedel) and finished goods (beverages from suppliers) and also packaging materials. The results of this research shows that the internal audit of stock on PT Fastfood Indonesia Tbk, KFC Ekalokasari branch outlet has two main activities, which are manual bookkeeping and integrated system of bookkeeping. The intern audit of stock on PT Fastfood Indonesia Tbk is done by auditor staffs from intern audit department which is placed separately from other unit and directly responsible to the Board of Commisioners of PT Fastfood Indonesia Tbk that guarantee its independency. According to the intern audit that has been done on PT Fastfood Indonesia Tbk's stock of goods, we can perceive that inconsistently of the integrated system (barcode) was found in the operating, and the efficiency of some goods did not meet the standards Keyword : Internal Audit, Internal Control of Inventory